TREND KESUKAAN PARK AND RIDE DENGAN METODE STATE PREFERENCE - Yules Pramona Zulkarnain; Honest Hokyanet; Bazar Asmawi; Syahril Alzahri (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2023)
Palembang city government chose light rail transit (LRT) as public transportation to overcome the problem of traffic congestion. However, the use of public transportation in the city of Palembang is not optimal, so traffic jams occur, It is necessary to develop facilities that can attract people's interest in using public transportation. This research uses the Stated Preference Method to determine socio-economic characteristics, travel characteristics, and people's preferences for the development of Park and Ride facilities in Palembang City. The respondents for this research were 100 LRT transportation passengers. From the research results, it is known that the majority of passengers are college students, aged between 19-25 years, with an income of less than IDR 1,000,000 and the reason for traveling is for recreation or entertainment. Based on descriptive analysis to determine respondents' preferences for the development of the Park and Ride concept offered in the Stated Preference Survey, the results obtained from 6 (six) travel scenarios obtained a total of 2400 choices from 100 respondents. Travel by private vehicle (Option A) was chosen 1512 (63%) times, while travel by the Park and Ride system integrated with public transportation was chosen 888 (37%) times.